(5w-8)(1-w)=0

Simple and best practice solution for (5w-8)(1-w)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5w-8)(1-w)=0 equation:


Simplifying
(5w + -8)(1 + -1w) = 0

Reorder the terms:
(-8 + 5w)(1 + -1w) = 0

Multiply (-8 + 5w) * (1 + -1w)
(-8(1 + -1w) + 5w * (1 + -1w)) = 0
((1 * -8 + -1w * -8) + 5w * (1 + -1w)) = 0
((-8 + 8w) + 5w * (1 + -1w)) = 0
(-8 + 8w + (1 * 5w + -1w * 5w)) = 0
(-8 + 8w + (5w + -5w2)) = 0

Combine like terms: 8w + 5w = 13w
(-8 + 13w + -5w2) = 0

Solving
-8 + 13w + -5w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(-8 + 5w)(1 + -1w) = 0

Subproblem 1

Set the factor '(-8 + 5w)' equal to zero and attempt to solve: Simplifying -8 + 5w = 0 Solving -8 + 5w = 0 Move all terms containing w to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 5w = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 5w = 0 + 8 5w = 0 + 8 Combine like terms: 0 + 8 = 8 5w = 8 Divide each side by '5'. w = 1.6 Simplifying w = 1.6

Subproblem 2

Set the factor '(1 + -1w)' equal to zero and attempt to solve: Simplifying 1 + -1w = 0 Solving 1 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1w = 0 + -1 -1w = 0 + -1 Combine like terms: 0 + -1 = -1 -1w = -1 Divide each side by '-1'. w = 1 Simplifying w = 1

Solution

w = {1.6, 1}

See similar equations:

| 6x=5x+2(x-1)-x+b | | (x-4)-(3-2x)=(3x+4)-(6+x) | | ln(5x-12)=9 | | Y-a=26 | | n^2-2n-3=6 | | x^2+6x=130 | | (3+2i)(3+2i)=0 | | 10m=k^2 | | 4g+3=23 | | X^2+5-104=0 | | 3n=30-3 | | x=48 | | 6x^3-13x^2-8x= | | 14=-16t^2+24t+6 | | g(b+6)=7x-2 | | 2+m=3 | | -2h+5=5h-44 | | N^2+10=-5n | | 5n=26+4 | | 6x=11x^2 | | -5h+6=41 | | x-10+x+30=120 | | 3x+=5x-1 | | 2(7x-55)=7x-20-2x | | x-10=120 | | 4x+2(x+5)-3x=3x+20 | | 0=x^2-8x-4 | | g(7b)=7x-2 | | -3=-t^3+5t^2-2t | | 6x+17+x=-74 | | sin(5x)+cos(5x)=0 | | x*z=y*z |

Equations solver categories